2018
DOI: 10.3164/jcbn.17-53
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prenatal administration of low dose antibiotics on gut microbiota and body fat composition of newborn mice

Abstract: Several environmental factors during the prenatal period transgenerationally affect the health of newborns in later life. Because low-dose antibiotics have been used for promoting the growth of crops and livestock in agriculture, humans may have ingested residual antibiotics for several decades. However, the effect of prenatal administration of low-dose antibiotics on newborns’ health in later life is unclear. In the present study, we found that prenatal treatment of murine mothers with low-dose antibiotics in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The abundance of some taxa remained different over time, including higher abundance of bacteria in the Lachnospiraceae family, which has been associated with greater child weight [17], and lower abundance of Akkermansia muciniphila , a bacterium associated with metabolic health [18]. An experimental murine model [19] and an observational study in infants delivered preterm [20] also found that prenatal antibiotic exposure is associated with an altered infant microbiome composition. Other studies have found trimester-specific associations of antibiotics with fetal adipokines and birth weight [21], and observed that antibiotic exposure in the second trimester is associated with higher risk of childhood obesity [58].…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of some taxa remained different over time, including higher abundance of bacteria in the Lachnospiraceae family, which has been associated with greater child weight [17], and lower abundance of Akkermansia muciniphila , a bacterium associated with metabolic health [18]. An experimental murine model [19] and an observational study in infants delivered preterm [20] also found that prenatal antibiotic exposure is associated with an altered infant microbiome composition. Other studies have found trimester-specific associations of antibiotics with fetal adipokines and birth weight [21], and observed that antibiotic exposure in the second trimester is associated with higher risk of childhood obesity [58].…”
Section: Discussionmentioning
confidence: 99%
“…All samples were prepared according to methods described by Human Metabolome Technologies, Inc. (HMT) (HMT, Tsuruoka, Japan) and in previous reports [24][25][26]. Briefly, the cecum luminal content, stool, cecum, liver, urine, and plasma were immediately frozen in liquid nitrogen and stored at −80 • C until metabolite extraction.…”
Section: Metabolome Analysis By Capillary Electrophoresis Electrospramentioning
confidence: 99%
“…Evidence suggests that host–microbe interactions may extend beyond the local environment to peripheral tissues ( Marsland et al, 2015 ). Preclinical and human studies have demonstrated that maternal antibiotic administration during prenatal and intrapartum periods alters the bacterial composition and diversity of the offspring’s intestinal microbiota ( Gonzalez-Perez et al, 2016 ; Yoshimoto et al, 2018 ; Dierikx et al, 2020 ; Zimmermann and Curtis, 2020 ). Microbiota profiles play a crucial role in intestinal barrier function and intestinal maturation in germ-free mice and human infants ( Reinhardt et al, 2012 ; Sommer and Bäckhed, 2013 ; Kelly et al, 2015 ; Selma-Royo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%